From what they get sick and why university workers get away from working: 2009 year analysis - Fátima Neves do Amaral Costa; Lis Maria Benassi Cézar; Cássia Tiêmi Nagasawa Ebisui (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
It is a study, quantitative, which evaluated in 2009, the fact that they were during that period, apart from the different working employees who worked in four units of a public university in São Paulo, as well as the cause of the illness that caused this separation. The working framework, involving the workplace, duties performed and clearance period, it can be said that men and women who have been away from work for a longer time, had their assignments preferably linked to repetitive services. It was determined that the prevalent morbidities related to those followed mental disorders of the musculoskeletal system and connective tissue diseases. These findings drive necessary theoretical insights about the conditions of work environments where these workers as well as the satisfaction thereof, to identify and prevent aspects that generate conflicts, pressures and suffering in the workplace, which can trigger diseases.